Correlation between atrial fibrillation driver locations and complex fractionated atrial electrograms in patients with persistent atrial fibrillation. Issue 10 (12th September 2018) - Ammar‐Busch, Sonia; Reents, Tilko; Knecht, Sebastien; Rostock, Thomas; Arentz, Thomas; Duytschaever, Mattias; Neumann, Thomas; Cauchemez, Bruno; Albenque, Jean‐Paul; Hessling, Gabriele; Deisenhofer, Isabel
Abstract: Introduction: The aim of this study was to evaluate a spatial correlation between active atrial fibrillation (AF) drivers measured by electrocardiographic imaging and complex fractionated atrial electrograms (CFAEs) in patients with persistent AF. Methods: Sixteen patients with persistent AF were included. A biatrial geometry relative to an array of 252‐body‐surface‐electrodes was obtained from a noncontrast computed tomography scan. The reconstructed unipolar AF electrograms were signal‐processed (ECVUE™, CardioInsight Technologies Inc., Cleveland, OH, USA) to identify AF drivers. Before driver ablation, a biatrial mapping using the NavX system (St. Jude Medical, St. Paul, MN, USA) was performed to identify CFAEs. CFAE and driver regions were then quantified and compared. Results: AF was terminated by driver ablation in 11/16 (70%) patients. The mean number of ablated driver regions was 4 ± 1 per patient. The most frequent driver locations were the inferior left atrium and coronary sinus, the right pulmonary veins, and the right atrium. In 49/63 (78%) of the driver locations, more than 75% of the driver site showed CFAEs. The mean ablated driver area was 58 ± 24 cm 2 (19 ± 11% of total surface area). The mean CFAE area was 178 ± 59 cm 2 (49 ± 16%). The percentage of non‐ablated CFAE area was 76 ± 13% of total CFAEs. In 9/11 patients with AF termination, the termination site showed CFAEs. Conclusions: There is a significant overlap between AF driver regions identified by the ECVUE™ system and CFAE areas identified by the NavX system. AF driver regions are smaller and mostly embedded in larger CFAE areas. Selective ablation of drivers in CFAE areas seems sufficient to terminate persistent AF in the majority of patients.